Issues of National Identity in Cultural and Spiritual Manifestations - Qayumova Dilorom Quvondikovna (Genius Journals, 2022)
As is known, the XXI century-entered history as the information age. The flow of information is at such a level that, frankly speaking, we sometimes become slaves to them, we cannot even understand which one is useful to us, which one is harmful. As a result, the level of knowledge is shallow, some young people who do not have the potential to analyze events are entering various Gypsy ways. The importance and social political power of the mass media is becoming the weapon of some countries today. The importance of national shows that contribute to increasing the culture and raising the morale of people in our country is especially important in the education of young people. In this article, views and comments on the issues of national identity are made in cultural and spiritual shows
Keywords: Culture; Spirituality; Nationality; Identity